Moderasi Beragama dalam Kitab Tasawuf Al-Muntakhabāt karya KH. Ahmad Asrori Al-Ishaqi - Muhammad Zakki Muhtar (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
This paper aims to reveal the moderate attitude in the tarekat. Tarekat as practitioners of Sufism are considered a less tolerant group in carrying out religious behavior in society. This paper attempts to see the moderate and tolerant understanding in the book Al-Munta¬khabāt, which contains the teachings of philosophical, moral, and practice Sufism written by KH. Ahmad Asrori Al-Ishaqi in the early 21st century. Through a qualitative study with an intellectual social history approach and hermeneutics, this paper proves that the book is specifically a guide for tarekat practitioners. In addition, KH. Ahmad Asrori Al-Ishaqi as an author has contributed significantly in bringing the message of religious moderation to life in Indonesia, which can be seen in some of his important ideas in Al-Muntakhabāt. Besides using Arabic fusha, KH. Ahmad Asrori Al-Ishaqi also presented material on philosophical, moral and practice Sufism with Sufism scientific networks in Indonesia. Some of these ideas display the characteristics of Islam which are moderate (wasaṭiyyah), balanced (tawāzun) and tolerant (tasāmuḥ). This is important to be actualized in order to reaffirm the nature and moderate attitude in religion, both individuals and organizations, with the aim of eliminating radical Islamic thoughts that are not in accordance with the nation's ideology. Keywords: Al-Muntakhabāt, KH. Ahmad Asrori Al-Ishaqi, Religious Moderation and TQN Al-Usmaniyah. Tulisan ini bertujuan mengungkapkan sikap moderat dalam tarekat. Tarekat sebagai pengamal tasawuf dianggap sebagai kelompok kurang toleran dalam menjalankan laku beragama di masyarakat. Tulisan ini berupaya melihat pemahaman moderat dan toleran dalam kitab Al-Muntakhabāt, yang berisi ajaran tasawuf falsafi, akhlaki, dan amali yang dikarang oleh KH. Ahmad Asrori Al-Ishaqi pada awal abad ke-21. Melalui kajian kualitatif dengan pendekatan sejarah sosial intelektual dan hermeneutika, tulisan ini membuktikan bahwa kitab tersebut secara khusus merupakan pedoman para pengamal tarekat. Selain itu, KH. Ahmad Asrori Al-Ishaqi sebagai pengarang telah berkontribusi signifikan dalam menghidupkan pesan moderasi beragama di Indonesia, di antaranya terlihat dalam beberapa gagasan penting pemikirannya dalam Al-Muntakhabāt. Selain menggunakan bahasa Arab fusha, KH. Ahmad Asrori Al-Ishaqi juga menyajikan materi tasawuf falsafi, akhlaki dan amali dengan jejaring keilmuan tasawuf di Indonesia. Beberapa gagasan tersebut menampilkan karakteristik Islam yang moderat (wasaṭiyyah), seimbang (tawāzun) dan toleran (tasāmuḥ). Hal ini penting untuk diaktualisasikan demi meneguhkan kembali sifat dan sikap moderat dalam beragama, baik perseorangan maupun perkumpulan organisasi, dengan tujuan menghilangkan pemikiran Islam radikal yang tidak sesuai dengan ideologi bangsa. Kata kunci: Al-Muntakhabāt, KH. Ahmad Asrori Al-Ishaqi, Moderasi Beragama dan TQN Al-Usmaniyah.